Typhoid Fever: Etiology, Clinical Manifestations, Diagnosis, and Management - Ruby Bhadoriya (Recent Trends in Infectious Diseases, 2026)
Typhoid fever is a systemic and potentially life-threatening infectious disease caused by Salmonella enterica serotype Typhi, which primarily spreads through the fecal-oral route via ingestion of contaminated food and water. It continues to be a major global public health concern, particularly in developing and low-resource countries where poor sanitation, inadequate personal hygiene, and unsafe water supplies prevail. The disease is characterized by prolonged high-grade fever, abdominal discomfort, headache, loss of appetite, hepatosplenomegaly, and systemic toxicity, which can significantly impact an individual’s health and quality of life. Without timely diagnosis and proper treatment, typhoid fever may lead to severe and life-threatening complications, including intestinal perforation, gastrointestinal hemorrhage, septicemia, encephalopathy, and multi-organ dysfunction. Early detection through clinical evaluation and laboratory investigations, coupled with prompt initiation of appropriate antibiotic therapy and supportive care, is crucial to reducing morbidity and mortality. Furthermore, preventive strategies play a vital role in controlling the disease burden. These include ensuring access to safe drinking water, improving environmental sanitation, promoting proper hand hygiene, strengthening public health education, and implementing effective vaccination programs. A comprehensive approach that combines early diagnosis, effective treatment, and robust prevention measures is essential to curb the transmission and mitigate the overall impact of typhoid fever, especially in endemic regions.
Keywords: Salmonella typhi; Typhoid fever; diagnosis; management; nursing care; prevention